Spectral eigenfunction decomposition of a Fokker-Planck operator for relativistic heavy-ion collisions - Rizzi, Alessandro; Wolschin, Georg (The European physical journal. A, Hadrons and nuclei, 2024)
A spectral solution method is proposed to solve a previously developed non-equilibrium statistical model describing partial thermalization of produced charged hadrons in relativistic heavy-ion collisions, thus improving the accuracy of the numerical solution. The particle’s phase-space trajectories are treated as a drift-diffusion stochastic process, leading to a Fokker-Planck equation (FPE) for the single-particle probability distribution function. The drift and diffusion coefficients are derived from the expected asymptotic states via appropriate fluctuation-dissipation relations, and the resulting FPE is then solved numerically using a spectral eigenfunction decomposition. The calculated time-dependent particle distributions are compared to Pb-Pb data from the ATLAS and ALICE collaborations at the Large Hadron Collider.
Online veröffentlicht: 30. September 2024
Gesehen am 26.02.2025